Telaah Kritis Pemikiran Jasser Auda dalam Buku “Maqasid Al-Shariah as Philosophy of Islamic Law: A Systems Approach” - Muhammad Baiquni Syihab (AN NUR: Jurnal Studi Islam, 2023)
Jasser Auda was a Muslim intellectual who was known as a contemporary maqashid figure. But what was interesting about Jasser Auda's contemporary maqashid was the existence of a principle that prioritizes sharia maqashid over Islamic legal theory. It was not the same as the classical maqashid initiated by Iman al-Ghazali which revealed the maqashid sharia of Islamic law that was being applied in life in his era. The method used in this study was library research, namely the analysis of Jasser Auda's thoughts in his book entitled: "Maqasid Al-Shariah as Philosophy of Islamic Law: a Systems Approach". The study results showed that Jasser Auda considered that Islamic law needed to be open so that Islamic law could be renewed and was always alive, even according to him, its authenticity had been questioned again so that it needed to be reviewed. This justified the allegation that there were some Muslims who considered the Islamic world to be lagging behind and want progress in life in the Islamic world as the progress of life experienced in the West, but without abandoning their religious monotheism, as the West had abandoned its religious doctrines in politics, economics and law. . Here, Jasser Auda was one of several of these Muslims.